STRENGTHENING CHARACTER EDUCATION THROUGH SCHOOL CULTURE AT SMK SWASTA TELADAN TANAH JAWA - Herman Herman; Dumaris E. Silalahi; Partohap Saut Raja Sihombing; Bloner Sinurat; Yanti Kristina Sinaga; Muktar B Panjaitan; Christian Neni Purba; Bertaria Sohnata Hutauruk; David Togi Hutahaean; Tiarma Intan Marpaung; Marnala Pangaribuan; Lydia Purba; Bangun Munte; Tumpal Manahara Siahaan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2021)
Schools must recognize that school culture has an effect on the development of character in students. With the prevalence of numerous character flaws among students, it is expected that through school culture, students will be able to form their character through a school-based habit. Teachers at SMK Swasta Teladan in Tanah Jawa, Simalungun Regency, were the recipients of this community service. Thirty-three teachers were among those who took part in the socialization. This was a qualitative research project with a descriptive approach. The approaches used in this case are lectures and group discussions, with information being given first, followed by a question and answer session about the material. After having all methods provided, the results of the socialization through the school culture implementation possibly to be implemented to support the character education were: 1) cultivating religious tolerance values, 2) The implementation of school ceremonies, 3) implementation of working groups (PokJa) in schools, 4) The use of student-centered learning (student-oriented learning) during the learning process, 5) Using scouts in schools for students’ training to be more independent, and the last was prizes should be granted to students including all areas events, not only for academic areas. Last but not least, the role of school culture really can strengthen and support the character education for the students.